STUDI PENGARUH LAMANYA PEMAPARAN MEDAN MAGNET TERHADAP JUMLAH SEL DARAH PUTIH (LEUKOSIT) PADA TIKUS PUTIH (RATTUS NORVEGICUS) - Mas Sastika Wati, Ni Komang; Trisnawati, Ni Luh Putu; Artawan, I Nengah (BULETIN FISIKA; Vol 15 No 1 (2014): BULETIN FISIKA, 2014)
On the research effect of duration of exposure to the magnetic field to the number of leukocytes in the rat (Rattus Norvigicus) are observed. Magnetic fields interval used in this study is 300 Gauss till 500 Gauss with varying exposure time there are 2 hours per day, 3 hours, 4 hours, 5 hours and 6 hours each day for three days and the recovery period of 5 days was assumed. Based on the results. The leukocytes number of the rats were given exposure to a magnetic field tends to increase after a recovery period tends to decrease the number of leukocytes or nearly normal. For N > 1 means the recovery takes over five days, as the number of leukocytes is still far above normal. For N < 1 recovery time is estimated that nearly five days, as the number of leukocytes gradually approaching normal.